Ground penetrating radar: a case study for estimating root bulking rate in cassava (Manihot esculenta Crantz) - Delgado, Alfredo; Hays, Dirk B.; Bruton, Richard K.; Ceballos, H.; Novo, Alexandre; Boi, Enrico; Selvaraj, Michael Gomez (Springer, 2017)
Background